Keputusan Konsumen Menggunakan Ojek Sampit: Harga, Produk, Orang, dan Bukti Fisik - Restiyani, Lina; Desliniati, Nurfitri (Universitas Darwan Ali, 2022)
The study was conducted to analyze the effect of price, promotion, people, and physical evidence on PitJek's purchasing decisions. There are five independent variables in the study, namely price, promotion, people, and physical evidence, and the dependent variable is purchasing decisions. Data were obtained by distributing questionnaires to 100 samples who had used the services of PitJek (Sampit Ojek). Samples were taken using the accidental sampling technique. The research analysis method is quantitative with validity and reliability tests, the analysis technique is the outer and inner models. The results of the analysis show that each statement is declared valid and reliable. In the results of hypothesis testing, it is found that price has a positive effect on purchasing decisions for PitJek services, while the results of promotions, people, physical evidence, and income (control variables) do not affect the purchasing decisions of PitJek services